2022
DOI: 10.1055/s-0042-1756475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatment Methods on the Shear Bond Strength of Resin Composite/Zirconia for Intra-oral Repair of Zirconia Restorations

Abstract: Objective A durable resin/zirconia bond is essential for successful intra-oral repair of zirconia restorations. The purpose of this study was to evaluate the influence of two mechanical treatments followed by seven chemical treatments on the shear bond strength (SBS) of composite resin to zirconia. Materials and Methods In this in vitro study, 280 zirconia blocks (Y-TZP) were either air-abraded or bur roughened and divided into seven experimental groups (n = 20) in terms of primer/resin application: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our findings showing decreased bond strength post-thermocycling, agreed with similar studies by Lee and Lee (49) Fathpour et al, (50) and Ozcan et al (51) . These studies also concluded that thermocycling universally reduced shear bond values across all tested groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showing decreased bond strength post-thermocycling, agreed with similar studies by Lee and Lee (49) Fathpour et al, (50) and Ozcan et al (51) . These studies also concluded that thermocycling universally reduced shear bond values across all tested groups.…”
Section: Discussionsupporting
confidence: 93%
“…Two additional studies were procured through manual searching, leading to a comprehensive assessment of 181 studies in full text for eligibility. Ultimately, 77 studies [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , …”
Section: Resultsmentioning
confidence: 99%
“…In the majority of studies evaluating the SBS values of materials, the values were compared, but their clinical acceptability was not discussed. Some studies accept 9 MPa [39,40] or 10-13 MPa [41][42][43] as an acceptable SBS value, while others have suggested that this value should be at least 17.20 or 18 MPa [38,44]. In addition, a meta-analysis revealed that the clinically acceptable bond strength value for inter-material (composite-composite) adhesion remains unclear [18].…”
Section: Discussionmentioning
confidence: 99%